2007
DOI: 10.1371/journal.pone.0000204
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Origin of the New Developmental Superfamily DANGER

Abstract: Developmental proteins play a pivotal role in the origin of animal complexity and diversity. We report here the identification of a highly divergent developmental protein superfamily (DANGER), which originated before the emergence of animals (∼850 million years ago) and experienced major expansion-contraction events during metazoan evolution. Sequence analysis demonstrates that DANGER proteins diverged via multiple mechanisms, including amino acid substitution, intron gain and/or loss, and recombination. Diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 56 publications
(69 reference statements)
4
20
0
Order By: Relevance
“…The results plotted in Figure 2a reveal residues within the phosphotyrosine binding pocket and the hydrophobic pocket. These data are in excellent accord with the results of the study of Tokonzaba et al which demonstrate that both of these pockets are involved in phosphotyrosine-binding and lipid-binding by the SH2 domain of c-abl (Supplemental Figure 1a) (18). Further, many of the XLA-causing mutations themselves scored high in this analysis, in particular G302 and N365.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The results plotted in Figure 2a reveal residues within the phosphotyrosine binding pocket and the hydrophobic pocket. These data are in excellent accord with the results of the study of Tokonzaba et al which demonstrate that both of these pockets are involved in phosphotyrosine-binding and lipid-binding by the SH2 domain of c-abl (Supplemental Figure 1a) (18). Further, many of the XLA-causing mutations themselves scored high in this analysis, in particular G302 and N365.…”
Section: Resultssupporting
confidence: 90%
“…These simulations also isolate amino acids which are integral to, and surround the known phosphotyrosine and hydrophobic binding pockets. These data correlate well with the NMR study of Tokonzaba et al (18), which demonstrated that these pockets were involved in binding phosphatidylinositol (4,5) bisphosphate (PIP(4,5) 2 ) by the SH2 domain contained in Abelson murine leukemia viral oncogene homolog 1 (c-abl), a distant relative of Tec kinases (18). Moreover, phylogenetic analysis of Tec kinase SH2 domains indicate that this region is evolving more rapidly than the other homologous domains contained in this family, suggesting this is a site of functional innovation.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…22). This consistent initiation site allows rps-BLAST to extend an alignment even between highly divergent sequences (22,(40)(41)(42)(43). This strategy is designed to amplify and encode the alignments possible for any given query sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Although cnidarians have been characterized as simple or primitive organisms based on their morphology, molecular studies of specific gene families have revealed an unexpected level of genomic, genetic, and transcriptional complexity in N. vectensis compared with Caenorhabditis elegans and Drosophila melanogaster (Miller et al 2005;Technau et al 2005;Nikolaidis et al 2007). Similarly, recent studies on M. brevicollis have revealed that choanoflagellates express a number of exclusively animal signaling and adhesion protein families (King et al 2003;Abedin and King 2008) and have lent support to the notion that choanoflagellates represent the closest known relatives of animals.…”
Section: Origin and Evolution Of The Animal Forminsmentioning
confidence: 99%